PERANCANGAN VISUAL IDENTITY MAMA SPREY KOTA PADANG - ARIEF FEBRIANTO YUNUS, Dr. M. Nasrul Kamal, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Mama Sprey is a sprey and bed cover industry. The lack of prominent visual identity of Mama Sprey's products, so consumers from Mama Sprey do not know the name or brand of the products they buy.Mama Sprey needs a design of a visual identity to increase consumer attractiveness, form an identity for Mama Sprey and inform the products sold by Mama Sprey. Design goals so that people are more familiar with, understand and can attract consumers' attention to products marketed by Mama Sprey,The method used is Glass Box with 5W + 1H analysis (what, who, where, when, why and how) to find a solution to the problem at hand. This design resulted in a Manual Book design as the main media, and also supported by several other media namely: sales invoices, business cards, letters, envelopes, stamps, x-banners, totebags, stickers, posters and t-shirts.Keywords: Visual Identity, Sprey, Brands